Aflatoxigenic fungi and aflatoxins in Portuguese almonds - Rodrigues, P. (2012)
Aflatoxin contamination of nuts is an increasing concern to the consumer’s health. Portugal is a big producer of almonds, but there is no scientific knowledge on the safety of those nuts, in terms of mycotoxins. The aim of this paper was to study the incidence of aflatoxigenic fungi and aflatoxin contamination of 21 samples of Portuguese almonds, and its evolution throughout the various stages of production. All fungi belonging to Aspergillus section Flavi were identified and tested for their aflatoxigenic ability. Almond samples were tested for aflatoxin contamination by HPLC-fluorescence. In total, 352 fungi belonging to Aspergillus section Flavi were isolated from Portuguese almonds: 127 were identified as A. flavus (of which 28% produced aflatoxins B), 196 as typical or atypical A. parasiticus (all producing aflatoxins B and G), and 29 as A. tamarii (all nonaflatoxigenic). Aflatoxins were detected in only one sample at 4.97 μg/kg.